PENGARUH RASIO MOCAF DAN BUBUR RUMPUT LAUT (E. cottonii) TERHADAP KARAKTERISTIK KERIPIK BROWNIES - Soewondo, Galuh Ayuningtyas; Basuki, Eko; Cicilia, Siska (Fakultas Teknologi Pangan dan Agroindustri, Universitas Mataram, 2023)
Brownie chips are one of the brownie innovations with a crunchy texture and are made from wheat flour. An alternative substitute for wheat in making brownies is mocaf and seaweed pulp is added to improve its characteristics. This study aimed to determine the effect of the ratio of mocaf and seaweed pulp (E. cottonii) on the nutritional value, physical, and organoleptic properties of brownie chips. This study used a completely randomized design (CRD) with 5 treatments, namely ratio of mocaf and seaweed pulp (E. cottonii) P1 (100%:0%), P2 (90%:10%), P3 (80%:20%), P4 (70%:30%), P5 (50%:50%). Parameters observed were moisture content, crude fiber content, protein content, baking powder and organoleptic (aroma, taste, texture and color). Observations were analyzed using analysis of variance (Analysis of Variance) at the level of 5% using the application Co-State. Further test was carried out using the Least Significant Difference (LSD) for significant difference data. The results showed that the ratio of mocaf and seaweed pulp (E. cottonii) gave significantly different effect on moisture content, crude fiber, protein, breaking power and organoleptic tests (hedonics and scoring) texture and taste, but not significantly different on organoleptic tests (hedonics and scoring) aroma and color.The best treatment was obtained in P3 treatment (80%: 20%) with 4,03% moisture content, 3,37% crude fiber content, 4,92% protein content, 3,75N fracture power; and all organoleptic parameters including aroma, taste, texture and color were accepted by the panelists based on the hedonic test with a like level of preference.